Association of Economic Status, Parental Knowledge, and Parenting Style with Stunting Incidence Among Toddlers at Karawang Health Center, West Karawang District, Karawang Regency, 2025 - Krisna Mukti; Sudiono Sudiono; Saleh Budi Santoso (Department of Publication of Inspirasi Elburhani Foundation Desa. Pamokolan, Kecamatan Cihaurbeuti, Kabupaten Ciamis, Provinsi Jawa Barat, Indonesia, 2026)
Background The highest frequency of stunting in the West Java Health Office, according to 2023 data, the overall percentage of stunted children was 19.2% or 968,148 people. The prevalence of stunted toddlers in Karawang Regency was 1.54% (Ministry of Health, 2023). Stunting is caused by several variables, including the education of poor and wealthy parents. Children's nutritional conditions will improve in families with better wages because they will have easier access to health and education services. Stunting may be reduced indirectly by the family's socioeconomic position, including family income, parental education, maternal nutritional expertise, number of family members, and others. Purpose This study aims to determine the relationship between economic status, level of knowledge, and parenting patterns of parents with the incidence of stunting in toddlers in the working area of the Karawang Community Health Center, West Karawang District, Karawang Regency. Method This study uses a descriptive analytical method with a cross-sectional approach. The number of samples was 80 respondents taken using a purposive sampling technique. The research instruments consisted of questionnaires on economic status, knowledge level, parenting patterns, and toddler height measurements. Results: The chi-square test showed a significant relationship between economic status (p = 0.02), knowledge level (p = 0.01), and parenting patterns (p = 0.03) with the incidence of stunting in toddlers. The conclusion of this study is that lower economic status, lower knowledge level, and inappropriate parenting patterns tend to increase the risk of stunting in toddlers. It is hoped that parents will better understand the importance of nutrition and parenting patterns to prevent stunting.